1992
DOI: 10.1139/f92-186
|View full text |Cite
|
Sign up to set email alerts
|

Food Consumption of Juvenile Coho (Oncorhynchus kisutch) and Chinook Salmon (O. tshawytscha) on the Continental Shelf off Washington and Oregon

Abstract: The overall food consumption by juvenile coho (Oncorhychus kisutch) and chinook salmon (O. tshawytscha) along the continental shelf off Washington and Oregon was estimated for the summer months of 1981–84 using both a direct field and indirect bioenergetic approach. Both models yielded similar estimates but the consumption estimated by the bioenergetic model was 14.8 and 3.2% higher for coho and chinook salmon, respectively. In a given year, overall consumption increased throughout the summer, despite decreasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 13 publications
0
49
0
Order By: Relevance
“…Food daily ration can be determined completely from laboratory experiments (Walh & Stein 1991), from in situ experiments (Thorpe 1977, Boisclair & Leggett 1985,1988,1989, Garcia & Adelman 1985, Kolok & Randorf 1987, Booth 1990, Sagar & Glova 1988, Walsh et al 1988, and often with a combination of both approaches (e.g. daily variations of food content weight determined in the field and food evacuation rate estimated in laboratory; Swenson 1977, Godin 1981, Brodeur & Pearcy 1987, Amundsen & Klemetsen 1988, Ruggerone 1989, Brodeur et al 1992). …”
Section: Introductionmentioning
confidence: 99%
“…Food daily ration can be determined completely from laboratory experiments (Walh & Stein 1991), from in situ experiments (Thorpe 1977, Boisclair & Leggett 1985,1988,1989, Garcia & Adelman 1985, Kolok & Randorf 1987, Booth 1990, Sagar & Glova 1988, Walsh et al 1988, and often with a combination of both approaches (e.g. daily variations of food content weight determined in the field and food evacuation rate estimated in laboratory; Swenson 1977, Godin 1981, Brodeur & Pearcy 1987, Amundsen & Klemetsen 1988, Ruggerone 1989, Brodeur et al 1992). …”
Section: Introductionmentioning
confidence: 99%
“…Although the physiological response of a salmon is known to vary with ontogeny (Brett 1995), we feel the application of this model is appropriate. Previous research has found model-predicted estimates of consumption by juvenile salmon to be within 10% of field and laboratory estimates derived independently (Beauchamp et al 1989;Brodeur et al 1992;Ruggerone and Rogers 1992).…”
Section: Discussionmentioning
confidence: 59%
“…Although this model was developed originally for adult Chinook salmon, previous research has found model-predicted estimates of consumption by juvenile salmon to be within 10% of independently generated field and laboratory estimates (Beauchamp et al 1989;Brodeur et al 1992;Ruggerone and Rogers 1992). Thus, the model is appropriate for the analysis of juvenile Chinook salmon energetics.…”
Section: Bioenergetics Modelmentioning
confidence: 99%
“…Aydin et al, 2005;Ballantyne et al, 2003;Beauchamp et al, 2004;Brodeur et al, 1992;Cech and Myrick, 1999;Madenjian et al, 2004;Petrell and Jones, 2000;Stewart and Ibarra, 1991) are often limited to a particular size range of individuals and to a particular species. However, to fully understand the cumulative impact of stressors at different life stages, and how management and restoration actions could impact salmon populations, we need tools that connect the different life stages and their environments.…”
Section: Example: Pacific Salmonmentioning
confidence: 99%